Aplikasi Artificial Intelligence Pendeteksi Jenis Spesies Hewan Menggunakan Metode Image Tracking Berbasis Android - Hary Krishna; Thoyyibah.T (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The animal type detection application was built to make it easier for humans to find information and educate on the introduction of animal types. It is very important to add knowledge and insight about animals so that you know the types and names of these animals. The system used to realize this project uses an Artificial Intelligence (AI) system. The system was built based on Android using the image tracking method (Vuforia) which is capable of detecting image target markers. The animal species detection system has been successfully implemented as a system model that is able to provide information such as name, species, population, habitat and others.